2015
DOI: 10.18065/rag.2015v21n2.10
|View full text |Cite
|
Sign up to set email alerts
|

Fenomenologia da percepção extracorpórea: análise de experiências fora do corpo

Abstract: Diversos autores apontam conceitos e etiologias para o fenômeno de Experiências Fora do Corpo (EFC). O presente artigo objetivou descrever e analisar as EFC a partir da experiência do vivido, elencando diferentes experiências denominadas EFC, comparando-as entre si e com o conceito científico de EFC, e investigando os sentidos dados a estas, bem como seu papel na vida cotidiana daqueles que alegam praticá-las, de modo a explorar as variedades de experiências rotuladas como EFC. Treze sujeitos foram entrevistad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Some authors have suggested that depending on how questions are framed (including cases in which belief and experience are evidently mixed in the wording of the question), the features or the prevalence of AEs might vary substantially (Alvarado, 2000; Irwin, Dagnall, & Drinkwater, 2013). When asked to describe a personal OBE, respondents may provide very different descriptions, including lucid dreaming and sleep paralysis (Medeiros & Silveira, 2015).…”
Section: Cultural and Group Differences In The Report Of Aesmentioning
confidence: 99%
“…Some authors have suggested that depending on how questions are framed (including cases in which belief and experience are evidently mixed in the wording of the question), the features or the prevalence of AEs might vary substantially (Alvarado, 2000; Irwin, Dagnall, & Drinkwater, 2013). When asked to describe a personal OBE, respondents may provide very different descriptions, including lucid dreaming and sleep paralysis (Medeiros & Silveira, 2015).…”
Section: Cultural and Group Differences In The Report Of Aesmentioning
confidence: 99%
“…Ao estudar as experiências fora do corpo, Medeiros (2014), por exemplo, demonstra o quanto, para alguns experienciadores, tais vivências "se definem por seu alto teor espiritual/religioso, sendo muitas vezes entendida como mediunidade e trazendo, em diversas vezes, conteúdos morais, como sobre a necessidade da caridade ou mesmo entendendo a EFC como forma de praticar a caridade" (p. 45).…”
Section: Outros Estudosunclassified